2018
DOI: 10.1371/journal.ppat.1006718
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific transcriptome analyses provide new insights into GPCR signalling in adult Schistosoma mansoni

Abstract: Schistosomes are blood-dwelling trematodes with global impact on human and animal health. Because medical treatment is currently based on a single drug, praziquantel, there is urgent need for the development of alternative control strategies. The Schistosoma mansoni genome project provides a platform to study and connect the genetic repertoire of schistosomes to specific biological functions essential for successful parasitism. G protein–coupled receptors (GPCRs) form the largest superfamily of transmembrane r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 88 publications
(102 reference statements)
0
30
0
Order By: Relevance
“…The large number of eggs produced by mature females plays a central role in the pathology of infection with this parasite and in disease spread. Previous research suggested that the sexual development of the female schistosome depends on appropriate signals provided directly or indirectly by the male during pairing [4][5][6][7][8][9][10][11][12][13]. Thus, understanding the mechanism of female development as a consequence of pairing may lead to novel concepts for impeding egg production to lessen the spread of schistosomiasis.…”
Section: Introductionmentioning
confidence: 99%
“…The large number of eggs produced by mature females plays a central role in the pathology of infection with this parasite and in disease spread. Previous research suggested that the sexual development of the female schistosome depends on appropriate signals provided directly or indirectly by the male during pairing [4][5][6][7][8][9][10][11][12][13]. Thus, understanding the mechanism of female development as a consequence of pairing may lead to novel concepts for impeding egg production to lessen the spread of schistosomiasis.…”
Section: Introductionmentioning
confidence: 99%
“…BAs typically signal through G-protein-coupled receptors (GPCRs), however, the current knowledge of BA GPCRs in schistosomes is fragmented ( Hahnel et al, 2018 ). DA, HA and 5HT GPCRs have been characterized in S. mansoni ( Taman and Ribeiro, 2009 ; El-Shehabi and Ribeiro, 2010 ; El-Shehabi et al, 2012 ; Patocka et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…576 In adult worms, GFVRIamide is localized to neurons that run along the cerebral commissure 577 towards the oral sucker [89]. Allatostatin receptor, a GPCR with ovary-specific transcription in 578 adult S. mansoni [86], is important for reproductive development in Schistosoma japonicum 579 adult females [91]. Four transcripts homologous to allatostatin receptor were expressed 580 primarily in shedding S. mansoni replicates.…”
mentioning
confidence: 99%
“…Praziquantel has been identified as a GPCR ligand acting to modulate serotoninergic 538 signaling[83]. Several in silico studies identifying and characterizing the S. mansoni 539 "GPCRome"[84,85] culminated in the classification of a broad range of phylogenetically distinct 540 clades/classes of GPCRs[86]. S. mansoni microarray studies have reported diverse expression 541 patterns of individual GPCRs, with the overall highest expression occurring in 3-7 week worms,542 indicating that they are associated with complex stage-specific roles[29,86].543 In intramolluscan stages, we identified 78 GPCR transcripts from our Illumina samples, and 544 26 probes from microarray samples(Fig 8).…”
mentioning
confidence: 99%
See 1 more Smart Citation